Evidence for higher twist effects in fast π- production by antineutrinos in neon - Fitch, P; Kasper, P; Cooper-Sarkar, A; Aderholz, M; Armenise, N; Azemoon, T; Bertrand, D; Berggren, M; Bullock, F; Calicchio, M; Clayton, E; Coghen, T; et al. (Springer-Verlag, 1986)
Evidence for a significant higher twist contribution to high z π- production in antineutrino scattering is presented. In events with W>3 GeV and Q2>1 GeV2 in our data, it accounts for (51 ±8)% of all π- with z above 0.5. It is consistent with the z-Q2 correlations of Berger's higher twist prediction. The data are inconclusive concerning the predicted y-z correlation and pT dependence. The z -Q2 correlation is not adequately described by the Lund Monte-Carlo. © 1986 Springer-Verlag.